(3SjQ GdaRGQis - (3CHh ESMGb,J (B188 (3g` s
(3ChdgG (B:s
(3HGH eG jaSO ai CQV GdYOh s
(3BNQgG (B:s
(3COfhG ai SHjd Gddg bOQ QeM Ch QeMjf Ke eQ Ydjg hbOOfG bOQeM gPG BNQ cJGH GdSjQai cJGH CHj eQhGf s
(3YdjgG bQGAI Ydi YHGS Hf CUHY hJedc HNWg SfI (B386s
(3fSNI KGfjI hBNQ HNW GdeDQN Nda Hf YHO Gdedc GdeYQha HGHf HTchGd GdeJhai SfI (B578s
(3fSNI Ydi Qb ZRGd s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B59s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJGQjNs